2020
DOI: 10.9739/tjvs.2020.663
|View full text |Cite
|
Sign up to set email alerts
|

Our experiences with the surgical repair of traumatic vascular injuries

Abstract: Objectives:The aim of this study is to report our experiences about the surgical repair of traumatic vascular injuries.Patients and methods: Between January 2011 and July 2019, 164 patients (151 males, 13 females; mean age 35.6±13.8 years; range, 6 to 77 years) who underwent emergency surgery due to vascular injuries were included in this retrospective study. Operative techniques, causes for injury, and patient outcomes were analyzed. Data were collected from the patient records.Results: Repair for major arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…[10] Ekim and Tuncer [12] performed end-to-end anastomosis in 28 of 49 cases in the management of brachial artery injuries. This technique was also the most preferred treatment option in the management of traumatic vascular injuries by Halıcı et al [11] In parallel with the literature, in present study, SFG and primary repair were the most frequently performed methods for TEAI.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…[10] Ekim and Tuncer [12] performed end-to-end anastomosis in 28 of 49 cases in the management of brachial artery injuries. This technique was also the most preferred treatment option in the management of traumatic vascular injuries by Halıcı et al [11] In parallel with the literature, in present study, SFG and primary repair were the most frequently performed methods for TEAI.…”
Section: Discussionsupporting
confidence: 74%
“…The type of vessel injured plays an important role in the treatment decision and in determining the patient's chances of survival. Halıcı et al [11] showed that radial artery and popliteal arteries were most commonly injured arteries in the upper and lower extremity, respectively. However, Khan et al [2] found popliteal artery to be the most commonly injured lower extremity artery, while they found brachial artery was the most common injured in the upper extremity.…”
Section: Discussionmentioning
confidence: 99%
“…[4] These life-threatening serious injuries can cause loss of limb function or limb loss if they are not treated timely and appropriately. [4,6] Multisystemic organ failure associated with COVID-19 requires a multidisciplinary approach by many specialists. Among these, radiologists, neurologists, cardiovascular surgeons and cardiologists with interventional radiology experience play an important role in this field.…”
Section: Discussionmentioning
confidence: 99%
“…The patients in the vascular surgery group were evaluated retrospectively in terms of accompanying comorbid diseases, injury sites, type of anesthesia, surgical procedure, operation time, complications, intensive care and hospital stay and followup results. [4,6] The patients in the interventional group were evaluated retrospectively in terms of comorbid diseases, type of interventional or endovascular treatments, duration of procedure, type of anesthesia, and complications. [7] The demographic data and procedural details of both groups are shown in Table 1 and Table 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation